The complete chloroplast genome of Akebia quinata (Lardizabalaceae) and phylogenetic analysis - Min, Jie (Mitochondrial DNA B Resour, 2020)
Akebia quinata is an herb medicine plant in traditional oriental medicine in China. In this current study, we had assembled the complete chloroplast genome of A. quinata. The complete chloroplast genome sequence of A. quinata has a total 157,817 bp in size and has a typical quadripartite structure, which is the same as other plant species chloroplast genome. It contained a large single-copy (LSC) region of 86,544 bp, a small single-copy (SSC) region of 18,989 bp and two inverted repeat (IR) regions of 26,142 bp. The complete chloroplast genome sequence contains 132 genes, including 87 encoding genes, 37 transfer RNA genes, and eight ribosomal RNA genes. One of IR region harbors seven protein encoding genes, seven tRNA genes, and four rRNA genes. Phylogenetic analysis result showed that A. quinata is closely related to Decaisnea insignis of the family Lardizabalaceae using the maximum-likelihood (ML) method in this study.